PENGUATAN NILAI-NILAI MODERASI BERAGAMA MELALUI PENDIDIKAN PASRAMAN NONFORMAL - Putera, Gusti Ngurah Ketut (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
The background of this study highlights the pervasive threat of radicalism and intolerance within the educational environment, impacting a portion of students and scholars with anti-Pancasila views, thereby posing a danger to social harmony. Urgent measures are necessary to address this situation before more widespread damage occurs. Employing a qualitative and exploratory approach, this research aims to develop an educational framework within the Non-Formal Pasraman in West Lombok Regency, West Nusa Tenggara Province. Both primary and secondary data are collected and analyzed using an inductive method. In efforts to curb radicalism, Pasraman adopts a preventive approach, focusing on the soft approach. Strategies such as introducing moderation values, exhibiting positive behavioral models, interfaith dialogue, active learning, and engaging in social services are identified as means to fortify the inculcation of religious moderation values. Strategic recommendations to enhance the quality of religious moderation education in non-formal Pasraman involve improving teacher qualifications, collaborating with relevant institutions, developing pertinent learning resources, and fostering inclusive and diverse educational approaches